Cambios morfométricos en huevos de Rhodnius prolixus (Heteroptera: Reduviidae) durante su desarrollo - Chaves, Luis Fernando; Ramoni-Perazzi, Paolo; Lizano, Eliézer; Añez, Néstor (ENTOMOTROPICA, 2007)
We explore morphometric changes during development in 124 eggs of Rhodnius prolixus, kept under laboratory conditions. Measurements were performed using a dissecting microscope coupled to a video camera connected to a monitor. Our results show that only maximal diameter varies significantly (t = 14.61, d.f. = 123, P < 1,19*10-18) changing from (0.88 ± 0.05) mm to (0.93 ± 0.04) mm. Such changes are correlated in a positive way according to a linear function (R2= 0.63; F= 206.29; d.f.= 1, 121; P<0.0001). The increase of this measurement is mainly explained by the intercept value (A= 0.186 ± 0.052; t= 3.57; d.f.= 120; P < 5*10-4), and this value could represent the maximun elasticity of eggs in this species.